The first brain : the neuroscience of planarians - Pagán, Oné R. (Oxford University Press, 2014)
The story of planarians, and their use as an animal model for many types of research in neuropharmacology. The book shows how research involving planarians has led to developments in biomedicine, neurobiology, and how planarians have been involved in popular biological and cultural topics.